Trends in Measurement Techniques in Laying Hen Farm Welfare: A Review - Rodriguez-Hernandez, R.; Lozano-Villegas, K. J.; Rondón-Barragán , I. S.; Oviedo-Rondón, E. O. (Tropical Animal Science Journal, 2026)
Animal welfare is a crucial issue in animal production, and researchers are seeking optimal methods to evaluate animal welfare in the field. In poultry farming, laying hen health and welfare are critical to consumer perception of product quality. The aim of the review was to examine traditional and advanced measurement trends of animal welfare in laying hens’ farms. Emerging technologies have facilitated a more profound comprehension of animal responses to diverse scenarios encountered in livestock production systems. Currently, conventional methods, such as behavioral observations, are time-consuming and highly dependent on the experienced observer’s expertise; likewise, other valuable indicators, including physiological parameters, hormonal levels, thermographic changes in the body, and hematological parameters, are widely used but are being re-evaluated. Currently, technological advances are developing comparatively non-invasive methods for multiple and long-term monitoring, such as machine vision and deep learning algorithms to track bird behavior. In addition, molecular techniques have emerged as promising tools to understand the cellular responses under internal or external stressful conditions and improve farm animal welfare. However, several challenges exist in terms of standardization and implementation of the new technologies, especially in developing countries. These challenges include limited access to advanced tools, costs, among others, and hinder implementation. In this review, we conclude that welfare research requires a holistic and interdisciplinary approach, utilizing both conventional measurements and new technologies to enable a more comprehensive assessment of animal welfare.